RUNX1, an androgen- and EZH2-regulated gene, has differential roles in AR-dependent and -independent prostate cancer - Takayama, Ken-ichi (Oncotarget, 2014)
Androgen receptor (AR) signaling is essential for the development of prostate cancer. Here, we report that runt-related transcription factor (RUNX1) could be a key molecule for the androgen-dependence of prostate cancer. We found RUNX1 is a target of AR and regulated positively by androgen. Our RUNX1 ChIP-seq analysis indicated that RUNX1 is recruited to AR binding sites by interacting with AR. In androgen-dependent cancer, loss of RUNX1 impairs AR-dependent transcription and cell growth. The RUNX1 promoter is bound by enhancer of zeste homolog 2 (EZH2) and is negatively regulated by histone H3 lysine 27 (K27) trimethylation. Repression of RUNX1 is important for the growth promotion ability of EZH2 in AR-independent cells. In clinical prostate cancer samples, the RUNX1 expression level is negatively associated with EZH2 and that RUNX1 loss correlated with poor prognosis. These results indicated the significance of RUNX1 for androgen-dependency and that loss of RUNX1 could be a key step for the progression of prostate cancer.